Automatic generation of suggestions for program investigation. - Robillard, Martin P. (Software engineering notes.)
Before performing a modification task, a developer usually has to investigate the source code of a system to understand how to carry out the task. Discovering the code relevant to a change task is costly because it is an inherently human activity whose success depends on a large number of unpredictable factors, such as intuition and luck. Although studies have shown that effective developers tend to explore a program by following structural dependencies, no methodology is available to guide their navigation through the typically hundreds of dependency paths found in a non-trivial program. In this paper, we propose a technique to automatically propose and rank program elements that are potentially interesting to a developer investigating source code. Our technique is based on an analysis of the topology of structural dependencies in a program. It takes as input a set of program elements of interest to a developer and produces a fuzzy set describing other elements of potential interest. Empirical evaluation of our technique indicates that it can help developers quickly select program elements worthy of investigation while avoiding less interesting ones.